A Study of Personal Characteristics, Leadership, and Workplace Environment Affecting Work Achievement of In-bound Tourist Guide (Foreign Language-Specific Area) - Pachimsawat, Pitsuphar (Journal of Cultural Approach, 2015)
The objectives of this study were to (1) study the difference of personal characteristics affecting work achievement of In-bound tourist guide (foreign language - specific area) (2) study the impact of the leadership factor and work place atmosphere factor affecting work achievement of In-bound tourist guide (foreign language-specific area), and (3) study the relationship of work achievement,which was composed of role of work satisfaction, work completion, and competitiveness factors. The statistical analysis was descriptive and inferential statistics. The inferential statistics was t-test, One-way ANOVA, multiple regression analysis, Pearson product-moment correlation coefficient. The results of this study revealed that the difference in gender was found not affected work achievement. On the other hand, the differences in age, educational level, and length of working factors were found affected work achievement. The work place atmosphere factor was found affected work achievement but the leadership factor was not found affected work achievement. Moreover, the relationships among the role of work satisfaction, work completion, and competitiveness factors of work achievement were found correlated with a significant level of 0.05.